2009
DOI: 10.1007/s12519-009-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Airway foreign body removal by flexible bronchoscopy: experience with 1027 children during 2000–2008

Abstract: Flexible bronchoscopy is useful and safe in retrieving airway foreign bodies in children. With skilled personnel and perfect equipments, flexible bronchoscopy could be considered as the first choice for the removal of airway foreign body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
180
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(197 citation statements)
references
References 25 publications
7
180
0
10
Order By: Relevance
“…The average delay between the development of symptoms and the diagnosis of FB aspiration ranged from 10 days to 11 months in previous studies (6,7,12) and a longer delay (15 month on average) was observed in our study. This is different from children, in whom a delayed diagnosis is rare (10,13,14). This is believed to be related to the fact that FBs lodged in the proximal airways (trachea and main bronchus) are probably more prone to be symptomatic than FBs located in peripheral airways.…”
Section: Discussionmentioning
confidence: 89%
“…The average delay between the development of symptoms and the diagnosis of FB aspiration ranged from 10 days to 11 months in previous studies (6,7,12) and a longer delay (15 month on average) was observed in our study. This is different from children, in whom a delayed diagnosis is rare (10,13,14). This is believed to be related to the fact that FBs lodged in the proximal airways (trachea and main bronchus) are probably more prone to be symptomatic than FBs located in peripheral airways.…”
Section: Discussionmentioning
confidence: 89%
“…In children with lower airway FBA, the most prevalent radiographic findings are listed in Table 3 (27,28,41,42).…”
Section: Diagnosismentioning
confidence: 99%
“…Alternatively, flexible (rather than rigid) bronchoscopy is utilized to extract the FB in some centers with experience in this technique (28,51,56,57). This technique customarily is circumscribed to older adolescents or adolescent adults.…”
Section: Mediastinal Shiftmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have also recommended the use of flexible bronchoscopes for the management of FB aspiration in children [154,155], and in some centres this has become the most frequently used option. In this context, ASLAN et al [156] presented a case documenting the importance of follow-up flexible bronchoscopy, even after successful FB removal with a rigid instrument.…”
Section: Paediatric Bronchologymentioning
confidence: 99%